Pseudocapacitive Charge Storage in Single-Step-Synthesized CoO-MnO2-MnCo2O4 Hybrid Nanowires in Aqueous Alkaline Electrolytes - Harilal, Midhun; Krishnan, Syam G.; Yar, Asfand; Izan Izwan, Misnon; Reddy, M. Venkatashamy; M. M., Yusoff; Dennis, John Ojur; Rajan, Jose (American Chemical Society, 2017)
A new pseudocapacitive combination, viz. CoOMnO2−MnCo2O4 hybrid nanowires (HNWs), is synthesized using a facile single-step hydrothermal process, and its properties are benchmarked with conventional battery-type flower-shaped MnCo2O4 obtained by similar processing. The HNWs showed high electrical conductivity and specific capacitance ( Cs) (1650 Fg −1 or 184 mA h g −1 at 1 A g−1) with high capacity retention, whereas MnCo2O4 nanoflower electrode showed only one-third conductivity and one-half of its capacitance (872 F g−1 or 96 mA hg −1 at 1 A g−1) when used as a supercapacitor electrode in 6 MKOH electrolyte. The structure −property relationship of the materials is deeply investigated and reported herein. Using the HNWs as a pseudocapacitive electrode and commercial activated carbon as a supercapacitive electrode we achieved battery-like specific energy ( Es) and supercapacitor-like specific power ( Ps) in aqueous alkaline asymmetric supercapacitors (ASCs). The HNWs ASCs have shown high Es (90 Wh kg−1) (volumetric energy density Ev ≈ 0.52 Wh cm −3) with Ps up to ∼104 W kg −1 (volumetric power density Pv ≈ 5 W cm −3) in 6 M KOH electrolyte, allowing the device to store an order of magnitude more energy than conventional supercapacitors.